PENGELOLAHAN GAJI DENGAN SPREADSHEET DALAM MENDESAIN LEMBAR KERJA MENGGUNAKAN RUMUS VLOOKUP, HLOOKUP, ALAMAT ABLOSUT DAN DATA ABSOLUT UNTUK MENGHASILKAN SLIP GAJI SMK BINA KARYA INSAN, TANGERANG SELATAN - Simarmata, Simon; Karo Karo, Panser; Jamaluddin (JAMAIKA: JURNAL ABDI MASYARAKAT, 2025)
Programming is the process of creating instructions that can be executed by a computer to perform specific tasks. This process can be analogized to a robot capable of carrying out simple activities, such as picking up toys or drawing. In order for the robot to perform these tasks, clear and systematic instructions must be provided. Programming, therefore, refers to the process of constructing such instructions so that computers or robots are able to understand and execute them; these instructions are commonly referred to as code or programs. Programming plays a crucial role in the professional world, as it opens up extensive career opportunities and enhances problem-solving skills. Through learning programming, individuals are able to develop applications, websites, games, or tools that can be utilized by others, thereby fostering creativity and deepening technological understanding. It motivate lecturers from the Informatics Engineering Study Program, Universitas Pamulang, to share their knowledge and experience with students of SMK BINA KARYA INSAN, a private vocational school located in Pondok Benda, Pamulang, South Tangerang. The implementation of this training program aims to enhance students’ knowledge and interest in understanding programming more comprehensively. It is expected that this training will broaden students’ perspectives and increase their awareness of the importance of computer technology, particularly in the field of programming. This community service activity was conducted by lecturers from the Faculty of Computer Science, Informatics Engineering Study Program, Universitas Pamulang, under the title “Basic Training on Microsoft Excel / Spreadsheet for Students of SMK BINA KARYA INSAN, Ciputat, South Tangerang.” The initial stage of the program involved the installation of the required applications, carried out by the lecturer team from the Informatics Engineering Program of Universitas Pamulang. The subsequent stage consisted of delivering training sessions to the students of SMK BINA KARYA INSAN Ciputat. The presenters delivered the training material theoretically through presentations, with students acting as participants, listeners, and implementers. Following the theoretical session, the activity continued with hands-on practical sessions.  Keywords: Spreadsheet, Logika function, Data lookup,  String function